HUBUNGAN KEPERCAYAAN KESEHATAN DENGAN KEPATUHAN MINUM OBAT PADA PENDERITA DIABETES MELLITUS TIPE 2 - Istianna Nurhidayati; Fitri Suciana; Ida Zulcharim (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2019)
Diabetes mellitus in Klaten have increased, especially in Karangnongko health center in 2016 there were 15 (0.002%) patients and in 2017 there were 538 (0.05%). This study aimed to determine relationship of health beliefs with medication adherence in patients with type 2 diabetes mellitus in the Karangnongko health center. This research used descriptive analytic design with cross sectional approach. Sample this study was 44 respondents, obtained by purposive sampling technique. The instruments of data collection used questionnaires. The results of the Pearson correlation analysis concluded average age of respondents was 53 years, the youngest age was 40 years and the oldest was 63 years, the sex of female respondents (75.0%), education level of elementary school (50.0%), not working (56.8%), duration of diabetes mellitus <5 years (75.0%), fasting blood sugar> 126 mg / dl (88.6%), other perceived health problems (61.4%), drugs consumed biguanide (79.5 %). Health belief in this study at least 65, a maximum of 141 and an average of 112.66 ± 21,824. Medication adherence at least 3, a maximum of 8 and an average of 6.34 ± 1,413. Pearson correlation test results was a relationship of health belief with medication adherence (p = 0,000). Relation of health belief with medication compliance showed a moderate positive correlation with correlation coefficient value or r =0.489 which means the greater the confidence of health hence the higher compliance of drug in diabetes mellitus type 2 at Karangnongko Health Center. Health belief have a relationship with the adherence of taking drugs diabetes mellitus type 2 at Karangnongko Health Center.